Biorevitalizing effect of a novel facial serum containing apple stem cell extract, pro‐collagen lipopeptide, creatine, and urea on skin aging signs. (1st October 2015) - Sanz, Maria Teresa; Campos, Celia; Milani, Massimo; Foyaca, Monica; Lamy, Amandine; Kurdian, Karine; Trullas, Carles
Summary: Background: Epithelial regeneration in skin is achieved by the constant turnover and differentiation of keratinocytes. Epidermal and dermal stem cells compartments are fundamental for the continuous renewal of the skin. Adult stem cells are the unique source for skin tissue renewal. Plants have stem cells and plant derived stem cell extracts are now used in topical products for their potential anti‐ageing and anti‐wrinkle effects. A new dermocosmetic product containing apple stem cell extract, urea, creatine and palmitoyl tripeptide‐38 (Ureadin Fusion Serum Lift Antiarrugas, ISDIN S.A), has been recently developed to target different aspects involved in skin aging. Study aim: To assess in vitro the effects of this new serum on the metabolic functions of human senescent fibroblasts and in vivo the anti‐aging effects by clinical and instrumental evaluation. Methods: We evaluated the effects of the serum on the mitochondrial ROS (reactive oxygen species) production in human senescent cultured fibroblasts measured at 0.1% and 1% using the Mitoread AntiOx mtROS method. In addition we evaluated the anti‐ageing in vivo effect of this new serum applied on the face twice daily for 28 consecutive days and assessed by clinical and instrumental evaluation in 32 women with sensitive skin bearing wrinkles on crow's feet. Results: The tested serum both at 0.1% and 1% induces a significant increase in 02 consumption, cellular ATP level and a reduction in extra‐cellular lactate concentration. The product reduces also significantly the mitochondrial ROS production. The clinical study shows a relevant anti‐wrinkle effect in 71% of the treated women with visible effects in 68% of the subjects as soon as 7 days of treatment. A significant increase in dermal density and skin elasticity was also observed. Conclusion: The use of this novel anti‐aging serum demonstrated a significant improvement of aging skin signs with first visible results achieved after one week of use. The product seemed to optimize the metabolic functions in human senescent cultured fibroblast restoring a more efficient cell metabolism therefore contributing to the anti‐aging properties of the product.